Model Edukasi Literasi Digital Berbasis Komunikasi Interpersonal: Strategi Peningkatan Resiliensi Masyarakat Desa terhadap Hoaks - Mukhamad Ainul Yaqin (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Rural communities in Lumbang District, Probolinggo, face high vulnerability to the spread of hoaxes due to limited access to verified information and trust-based communication patterns. The focus of this community service was to design and implement a digital literacy education model specifically based on an interpersonal communication approach to build collective resilience. The method used was Participatory Action Research, where the intervention was delivered through workshops modified into dialogical sessions, focused group discussions, and case studies, replacing one-way lecture methods. The results showed the model's significant effectiveness, evidenced by the increase in the average score of participants' verification skills from 35.4 in the pre-test to 78.2 in the post-test. The number of participants categorized as capable of verification also increased from 25.0% to 85.0%. This intervention proves that a dialogical, interpersonal approach is a key strategy for enhancing digital resilience in rural communities.